Evaluation of Integrated Social Welfare Data Management in Penajam Paser Utara District - Febrianto, Amirul; Djabar, Sadly Abdul; Wahyu, Wahyu (Journal La Bisecoman, 2023)
This study seeks to examine the influence of the efficacy of Social Welfare Integrated Data Management in Penajam Paser Utara Regency. The study was carried out at the Social Services and Villages Department in Penajam Paser Utara Regency. Data collection is conducted via observation, interviews, and documentation. This study employs a descriptive methodology utilizing a qualitative approach with inductive data analysis. Data analysis approaches employ data reduction, data display, and conclusion formulation or validation. The findings of this study indicated that the effectiveness of updating DTKS yields results due to monthly changes, including the addition of impoverished families and the removal of families deemed capable. Regarding the efficiency of DTKS management, it is acknowledged as more efficient in operations, data storage, and other technical aspects for both Data Managers at Dinas Sosial and Operators at Village Governments, in terms of adequacy. The quantity of social assistance recipients is substantial, yet the trend indicates a decline in recipients over time, reflecting a reduction in impoverished families in Penajam Paser Utara Regency. Regarding equity, it is evident that the Ministry of Social Affairs' social assistance program encompasses all 54 villages in the regency. In terms of responsiveness, The Dinas Sosial of Penajam Paser Utara Regency demonstrates considerable responsiveness in executing its activity budget program; however, at the Village Government level, the responsiveness regarding the management of DTKS is markedly deficient. While some villages are active, a significantly greater number have failed to update the DTKS.